Physiological Factors that Affect Mean Arterial Pressure in Post Trepanation Patiens - Sari, Erlina Kartika (Health Gate, 2024)
MAP (Mean Arterial Pressure) is the average arterial pressure required for blood circulation to the brain. In trepanation post op patients, MAP is an indicator of postoperative prognosis. This MAP is influenced by several physiological factors, namely heart rate, hematocrit and age. This study aims to determine and explain the effect of these three factors on MAP (Mean Arterial Pressure) in post-op trepanation patients at the Intensive Care Installation of Mardi Waluyo General Hospital, Blitar City. The design of this study is Cross-Sectional. Source of data used is secondary data. Data collection is done by observation method. The research sample was all medical records of trepanation post-op patients at the Intensive Care Installation of Mardi Waluyo Hospital, Blitar City who were treated from January to  December 2022 who met the inclusion criteria, totaling 42 respondents. Data analysis using binary regression with a significance degree of p value less than 0,05 (p<0.05). The results showed that the Nagelkerke R Square (Model Summary) value was 0.314. This shows that the contribution or influence of physiological factors (heart rate, hematocrit, age) on MAP is 31.4%, while the remaining 68.6% is determined by other variables that are not taken into account in this research model. It is suggested to health service providers, especially nurses, to further improve their ability to analyze critical values of patients to prevent worsening of the prognosis.